Administración y gestión de la traducción e interpretación, enfocado hacia negocios internacionales. (2020)
El main concept of this research was to analyze the way in which translation and interpretation are the views from the field of international business. Also, it starts by examining some basic concepts concerning these issues, the analysis in the literature is a comparative science between the differences that exist at the time of exercising this profession at a professional level in Colombia, Mexico, cited mainly from the government websites of both countries to discover the processes which lead to the professionalization of this, known in Colombia as “certified translators”, and in Mexico as “expert translators”, by referring to equally outstanding authors and specialized companies in the area. This research analyzes the technical mastery and professional in translation and interpretation associate as an alternative to paradigmatic. Also, the information above, it is mainly obtained from theoretical developments, cultural, political, offering not only the main approaches of the field, but an in-depth analysis of the benefits that this represents. In this sense, it concludes by recommending that the process of translation and interpretation are a process of intercultural interaction in the field of international business, more than just one lexical field of compartment units of one language or another.